Synergistic Effect of 𝘼𝙣𝙙𝙧𝙤𝙜𝙧𝙖𝙥𝙝𝙞𝙨 𝙥𝙖𝙣𝙞𝙘𝙪𝙡𝙖𝙩𝙖 with Medicinal Plants to Inhibit the Growth of Opportunistic Bacteria - Kongcharoensuntorn, Wisatre; Kuawaiyakul , Kanok; Thongsri, Sukanya (Burapha Science Journal, 2026)
The research was screening therapeutic potentials of plant extracts of Andrographis paniculata (Burm.f.) Wall.Ex Nees with eighteen medicinal plants. The results indicated that all medicinal plants had antibacterial activities against Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853 and Staphylococcus aureus 25923 (MIC = 0.625-80 mg/mL). However, antibacterial activities of all medicinal plants were less than antibacterial activities of oxytetracycline and ampicillin. The synergism results of A. paniculata combined with several medicinal plants were revealed that A. paniculata, mixed with Momordica charantia, Bouea macrophylla or Tagetes erecta, showed the most effective synergy to inhibit the growth of tested bacteria. Moreover, the most antibacterial activities of therapeutic medicinal plants, mixed with A. paniculate were indicated against P. aeruginosa ATCC 27853 of which showed 100% susceptibility. Finally, A. paniculata mixed with P. betle, and A. paniculata mixed with C. sappan, shown the best synergy effect, were confirmed by Checkerboard assay. The synergistic results indicated that A. paniculata, mixed with P. betle showed the best synergistic effect against S. aureus ATCC 25923 of which FICIs was 0.5. However, there was an exceptionally antagonist of antibacterial activity when using A. paniculata mixed with C. sappan against P. aeruginosa ATCC 27853 (FICI= 4.125). This research suggests that A. paniculate has synergy effect when mixed with P. betle against bacteria.